Detection of Arterial Occlusions Using Viscoelastic Wave Propagation (Advances in Applied Mathematics and Mechanics, 2018)
We consider the problem of detecting cardiac artery occlusionsusing stenosis driven viscoelastic (VE) waves propagated throughbiotissue to body surface sensors. We investigate possiblestatistical model formulations (ordinary least squares (OLS),generalized least squares (GLS)) and post analysis techniques(residual plots) to ascertain uncertainty in estimates as well asvalidity of the statistical models as part of a methodology forstenosis detection using viscoelastic waves.